From a ZIF-8 polyhedron to three-dimensional nitrogen doped hierarchical porous carbon: an efficient electrocatalyst for the oxygen reduction reaction. Issue 23 (23rd May 2018) - Xuan, Cuijuan; Hou, Baoshan; Xia, Weiwei; Peng, Zongkai; Shen, Tao; Xin, Huolin L.; Zhang, Guoan; Wang, Deli
Abstract : Three-dimensional nitrogen doped hierarchical porous carbons are synthesized by NaCl-assisted pyrolysis exfoliation of a ZIF-8 polyhedron with enhanced ORR electrocatalytic activities. Abstract : Nitrogen-doped carbon materials derived from metal–organic frameworks (MOFs) have been proposed as promising electrocatalysts for the oxygen reduction reaction (ORR) but still face a great challenge to replace Pt. In this work, a NaCl-assisted exfoliation approach was developed to synthesize three-dimensional (3D) nitrogen doped hierarchical porous carbons (NHPCs) by the pyrolysis of a ZIF-8 polyhedron. At high temperature, NaCl crystals become a molten salt which not only serves as a template wrapping ZIF-8 derived carbon but also as an intercalating agent penetrating through the carbon via capillarity to promote the formation of nanosheets and mesopores and prevent the aggregation of nanosheets. The morphology, graphitization degree and nitrogen type of the resulting carbons are effectively controlled by tuning the NaCl/ZIF-8 mass ratio and pyrolysis temperature. The as-prepared optimal carbons show an intertwined nanosheet structure with rich micro- and mesopores, high surface area, suitable graphitization degree and nitrogen type. Benefiting from these desirable features, the optimal NHPCs exhibit excellent ORR electrocatalytic performances, much better than Pt/C, and also show high capacity and outstanding long-term discharge stability in Zn–air batteries. This work provides a simple and appealing method to prepare hierarchical porous structured carbon materials, and has a great potential to be extended to other MOFs for energy-related applications.